Psychometric Properties of the HEXACO ‎Personality Inventory-Revised in a Jordanian ‎Context - Al-Saied‎, Saied; Al-Shrifeen, Nedal (Jordan Journal of Educational Sciences, 2023)
This study aimed to standardize the revised Six Factors of Personality Scale (HEXACO-PI-R) self-report version in the Jordanian context. Also, it aimed to find its psychometric properties. The descriptive methodology was used to achieve the aims of the study. The scale was translated from English to Arabic and administered to 703 university students (265 males and 438 females).They were selected using the available sample method from six public universities in the regions (North, Center, and South).The results of the study showed the presence of 25 factors in the Jordanian context. Additionally, six primary factors were found based on the principal components analysis results. The results showed that the scale has good validity and reliability indicators, as the values ​​of the reliability coefficients by Cronbach's alpha ranged between (0.67-0.78) at the level of the six main factors and (0.52-0.88) at the level of the twenty-five sub-factors. Also, the scale criteria were extracted from mean and standard deviations from the responses of the study sample members